Remote sensing of river habitat for salmon restoration - Giroux, Chantal; Grant, Jon; Brown, Craig J.; Barrell, Jeffrey (Frontiers in Remote Sensing, 2022)
Losses of river complexity and viable habitat has led to negative effects on Atlantic salmon. With the rapid population decline of Atlantic salmon, there has been an increase in river restoration and salmon reintroduction projects, and an understanding of substrate is a vital component in the restoration of these habitats. However, the isolation and/or inaccessibility of many of these rivers make the collection of this information challenging and expensive based on conventional survey approaches. This study looks at the feasibility and accuracy of conducting substrate analysis using low-cost uncrewed aerial vehicles (UAV) at seven transects on the Upper Salmon River located in Fundy National Park near Alma, New Brunswick, Canada. Using supervised classification and object-based image analysis, UAV use was evaluated for substrate delineation. The seven transects represent macroscale river habitats including riffles, runs and pools. The analysis was conducted with an accuracy of 79% for dry substrate and 86% for submerged substrate, demonstrating the potential of UAV use in river habitat analysis.